O impacto da política de favorecimento de micro e pequenas empresas nas compras públicas municipais para o desenvolvimento sustentável - Publio, Maria Christina Machado (2018)
The municipal purchases are, of course, a mechanism to support local development, through the financial transfer through hiring. Local companies become supporters of government action, through the generation of jobs and income. It is presumed that the world begins a period of crisis that will impose a disruption in the current model of organization of societies, with the advent of technological revolution and substantial impacts on economic and political transformation, according to Alves (2011). The major purpose of this research is to analyze the impacts of policies favoring MSE on public procurement to the sustainable development. The conceptual basis for this study is defined in two specific sections dealing with sustainable development and public procurement. Elkington's Triple Bottom Line (1999) was chosen for the analysis of sustainable development, for its proposal in three dimensions: social, economic and environmental. The research is exploratory, descriptive and quantitative. The secondary data used were obtained from the information base of the Court of Audit of the State of Ceará - TCE, Brazilian Service of Support to Micro and Small Enterprises - SEBRAE, Institute of Research and Economic Strategy of Ceará - IPECE and Brazilian Institute of Geography and Statistics - IBGE. The population of the research is composed by the 184 municipalities of the state of Ceará. The results of the survey showed that public purchases show a different and superior performance in the municipalities that implemented the MSE favoritisation policy, through the General Law, and that there is a significant relationship between the quantity of MSE contracted in public procurement municipal and municipal sustainable development indicators, in three dimensions: social, economic and environmental. Finally, it is verified that this research has made a relevant contribution in demonstrating the associations and possible causal relationships between the recent evolution of the municipalities of Ceará possibly driven by the policy of favoring micro and small companies in public procurement and its evidences in sustainable development. The research also leaves as a legacy the proposed framework that brings a conceptual complementarity, instigating the emergence of future methodologies, indicators and strategies in the field of study of the interface between public procurement and sustainable development.